2012
DOI: 10.4161/spmg.22602
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α-mediated restructuring of the Sertoli cell barrier in vitro involves matrix metalloprotease 9 (MMP9), membrane-bound intercellular adhesion molecule-1 (ICAM-1) and the actin cytoskeleton

Abstract: The mammalian blood-testis barrier (BTB) restructures throughout spermatogenesis, thereby allowing developing germ cells to enter the adluminal compartment of the seminiferous epithelium. Previous studies have shown pro-inflammatory cytokines such as tumor necrosis factor α (TNFα) and interleukin-1α to be important regulators of Sertoli cell barrier/BTB function in vitro and in vivo. In this study, the effects of TNFα on Sertoli cell barrier function were assessed, with emphasis on changes in proteases and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…For instance, early studies by flow cytometry showed the presence of ICAM1 on the surface of mouse Sertoli cells [173, 174]; however, the significance of this important finding probably went unknown to investigators at the time because cell junctions in the testis were largely uncharacterized structures in the early 1990s. In recent studies, we confirmed and expanded these initial findings by illustrating ICAM1 expression in both Sertoli and germ cells [49, 175]. Immunolocalization studies revealed ICAM1 to be present in all stages of seminiferous epithelial cycle, with ICAM1 staining surrounding the heads of elongating/elongated spermatids at stages IX–XIII of the seminiferous epithelial cycle where it likely participates in cell adhesion.…”
Section: 5 Icam1 and Sicam1 Function In The Testissupporting
confidence: 81%
“…For instance, early studies by flow cytometry showed the presence of ICAM1 on the surface of mouse Sertoli cells [173, 174]; however, the significance of this important finding probably went unknown to investigators at the time because cell junctions in the testis were largely uncharacterized structures in the early 1990s. In recent studies, we confirmed and expanded these initial findings by illustrating ICAM1 expression in both Sertoli and germ cells [49, 175]. Immunolocalization studies revealed ICAM1 to be present in all stages of seminiferous epithelial cycle, with ICAM1 staining surrounding the heads of elongating/elongated spermatids at stages IX–XIII of the seminiferous epithelial cycle where it likely participates in cell adhesion.…”
Section: 5 Icam1 and Sicam1 Function In The Testissupporting
confidence: 81%
“…associated with the degradation of TJPs (16,17). Therefore, we next determined if ZIKV infection could alter the expression of CAMs and MMPs in HSeCs.…”
Section: Resultsmentioning
confidence: 99%
“…This unique mechanism for the transit of spermatocytes requires a restructuring of the SCB via modulating tight junction proteins throughout spermatogenesis without compromising the homeostasis of the seminiferous tubules (9). However, cell adhesion molecules such as ICAM-1 and VCAM-1 and MMPs induced by inflammatory triggers, including TNF-␣ and IL-1␣, play a critical role in junction disruption and cell movement (16). The pattern of the ZIKV-induced response in the SCB is very similar to the WNV-BBB interaction.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 is a member of the immunoglobulin superfamily, which is typically expressed on the surface of endothelial cells to mediate the transmigration of leukocytes into the tissues (16). In the epithelial derived carcinoma, such as melanoma, the expression of ICAM-1 is correlated to the malignancy of the diseases (17).…”
Section: Discussionmentioning
confidence: 99%